Smoke-suppressing and low-toxicity adhesive for core-board, preparation method and application of smoke-suppressing and low-toxicity adhesive
By using phytic acid and glyceryl ether modified urea formaldehyde resin in joinery adhesives, combined with silicate minerals and hydroxyethyl starch with modified layered structures, the flame retardant performance and insufficient glue strength in the prior art are solved. The problem of high glue strength and low smoke release effect is achieved.
Patent Information
- Application Number
- CN202411371078.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-02-14
AI Technical Summary
In the prior art, the silicate mineral dispersion with modified layered structures is not obvious when used alone, it is easy to precipitate and has poor compatibility, resulting in a shortening of the adhesive's applicable life and affecting the adhesive strength and bending strength.
Phytic acid is used as an acid regulator, combined with glycerol ether modified urea-formaldehyde resin adhesive, and added silicate minerals and hydroxyethyl starch with modified layered structures to improve the adhesive by forming a stable coordination network and increasing flexible chain segments. Toughness and flame retardant properties.
The high glue strength, low smoke release and good flame retardant performance of the joinery board are achieved, the flame retardant performance reaches B1 level and the smoke release is low, and the ZA2 level can be reached by mouse poisoning test.
Smart Images

Figure CN119432277A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flame-retardant blockboard, and in particular to an adhesive for smoke-suppressed and low-toxic blockboard, a preparation method and application thereof. Background Art
[0002] Blockboard without flame retardant treatment is a flammable material. Once a fire occurs, the fire will spread rapidly, seriously threatening people's lives and property. In actual fires, one of the important reasons for casualties is the local sudden increase in the concentration of toxic smoke at the fire scene. Therefore, it is very necessary to inhibit the generation and release of toxic smoke when flame retardant blockboard is burned.
[0003] The modified layered silicate mineral dispersion is a natural ore with magnesium hydroxide as the main component and has a certain flame retardant effect. However, the flame retardant performance of the modified layered silicate mineral dispersion material used alone is not obvious. Generally, a large amount is added. During use, the flame retardant is easy to precipitate, and the compatibility is poor. It is easy to agglomerate, resulting in uneven dispersion, which shortens the application period of the adhesive. At the same time, the modified layered silicate mineral dispersion is alkaline, which affects the curing effect when combined with urea-formaldehyde resin, and reduces the bonding strength and bending strength.
[0004] Phytic acid (also known as inositol hexaphosphate, cyclohexane hexaphosphate) is an environmentally friendly, non-toxic, cheap, readily available and biocompatible organic phosphoric acid flame retardant. It contains up to 28% of the total molecular weight of phosphorus atoms in the inositol hexaphosphate structure and is stored as the main form of phosphorus in various plant tissues (seeds, roots and stems). However, pure phytic acid-modified wood has poor smoke suppression, poor thermal stability of the charcoal layer, and is easily oxidized and decomposed when heated.
[0005] Chinese patent CN114350293B discloses a method for preparing flame-retardant plywood. Microencapsulated red phosphorus, ammonium polyphosphate and aluminum hydroxide are used as compound flame retardants to improve the flame retardant properties of plywood. At the same time, the flame retardant is surface treated to reduce the impact on the bonding strength of plywood. The prepared flame retardant needs to be compounded with other commonly used flame retardants or modifiers to achieve a synergistic flame retardant effect. Compound flame retardants often require more expensive equipment, higher raw material costs, and more complex production processes. Chinese patent CN103481343B discloses a wood flame retardant treatment process. The drug loading rate of the Scotch pine solid wood treated with the modified process is significantly improved compared to the wood treated with the ordinary process, which effectively improves the flame retardant and smoke suppression properties of the wood. The prepared flame retardant is relatively hygroscopic, easy to lose, and easy to migrate to the surface of the material. It is easy to release a large amount of smoke and toxic gas during the flame retardant process, and the impregnation has a more complex process. Chinese patent CN114102776B discloses a process for preparing a wood flame retardant. This method for preparing flame-retardant wood by in-situ polymerization of aniline solves the problems of large addition amount of existing inorganic flame retardants, weak interface bonding and large smoke emission of some organic flame retardants to a certain extent. The patent requires that the wood be immersed in an acidic solution containing aniline, and then pressurized and maintained after evacuating to vacuum; after treatment, it is also necessary to immerse it in an acidic solution containing ammonium persulfate and stir it in an ice water bath. The flame-retardant wood prepared by this patented technology has good flame retardant and smoke suppression effects. However, polyaniline is not only expensive, but also has certain toxicity; and ammonium persulfate is a fifth-class oxidizing solid and a dangerous good. At the same time, the pressure is increased and maintained and the low-temperature heat preservation is required in the preparation process, which places high requirements on equipment and complex processes.
[0006] However, the flame retardant performance of the modified layered silicate mineral dispersion material used alone is not obvious, and the amount added is generally large. During use, the flame retardant is easy to precipitate and agglomerate, resulting in uneven dispersion, which shortens the applicable period of the adhesive and seriously affects the bonding performance of the artificial board, reducing the bonding strength and bending strength. It usually needs to be compounded with other substances. Summary of the invention
[0007] Based on the above determination, the present invention uses phytic acid as an acidic regulator to improve the preparation process of urea-formaldehyde resin adhesive, and adds glycerol ether modification during the preparation process to improve the toughness of urea-formaldehyde resin. The ether bond in glycerol ether is a flexible segment. After adding the flexible segment, a larger free space is generated, which softens the cross-linked segment and absorbs energy when it breaks to achieve a toughening effect. Phytic acid is composed of 6 phosphate groups and 12 hydroxyl groups and has a strong electronegativity. It can be combined with metal ions and positively charged compounds to form a stable coordination network with metal ions in the modified layered silicate mineral dispersion, reducing the agglomeration phenomenon of the modified layered silicate mineral dispersion; at the same time, the phosphorus content in the phytic acid molecule is high (28wt%), and it has a strong catalytic carbonization ability, which solves the problem that the modified layered silicate mineral dispersion has no obvious flame retardant performance, low strength, and poor toughness when used alone. At the same time, the prepared blockboard has high bonding strength, flame retardant performance up to B1 level, low smoke release, and can reach ZA2 level after mouse poisoning test. The content of the present invention is as follows:
[0008] The first object of the present invention is to provide an adhesive for smoke-suppressed and low-toxic blockboard, the technical point of which is that, measured by weight, it includes 100 parts by weight of a modified urea-formaldehyde resin adhesive and 30-50 parts by weight of a mixed filler; the modified urea-formaldehyde resin adhesive includes 300 parts by weight of a formaldehyde aqueous solution with a mass fraction of 25-50wt%, 10-30 parts by weight of an alkaline catalyst, 1-5 parts by weight of polyvinyl alcohol, 160-250 parts by weight of urea, 10-20 parts by weight of a phytic acid solution with a mass fraction of 50wt%, 10-30 parts by weight of sodium hydroxide with a mass fraction of 30-50wt%, 20-50 parts by weight of melamine (formaldehyde-preventing agent) and 10-30 parts by weight of glycerol ether (epoxy toughening modification).
[0009] In order to better realize the above technical scheme, the glycerol ether in the smoke-suppressed and low-toxicity adhesive for blockboard of the present invention is 1,4-butanediol glycidyl ether and at least one propylene triglycidyl ether.
[0010] In order to better realize the above technical scheme, the alkaline catalyst in the smoke-suppressed and low-toxic adhesive for blockboard of the present invention is at least one of sodium hydroxide and potassium hydroxide.
[0011] In order to better realize the above technical scheme, the mixed filler in the smoke-suppressed and low-toxic adhesive for blockboard of the present invention is a mixture of modified layered silicate mineral and hydroxyethyl starch, and the mass ratio of the modified layered silicate mineral and hydroxyethyl starch is 10:1.
[0012] In order to better realize the above technical scheme, the modified layered silicate mineral in the smoke-suppressed and low-toxic adhesive for blockboard of the present invention comprises a mixture of layered silicate mineral and a modifier, and the addition amount of the modifier is 0.5-5wt% of the layered silicate mineral.
[0013] In order to better realize the above technical scheme, the layered silicate mineral in the smoke-suppressing and low-toxic adhesive for blockboard of the present invention is at least one of brucite and sepiolite.
[0014] In order to better realize the above technical scheme, the modifier in the smoke-suppressing and low-toxicity adhesive for blockboard of the present invention is a cationic surfactant such as dodecyl dimethyl benzyl ammonium chloride.
[0015] The second object of the present invention is to provide a method for preparing a smoke-suppressed and low-toxic adhesive for blockboard, the technical point of which is that it comprises the following steps:
[0016] Step 1, pouring the formaldehyde solution into a three-necked flask, adding an alkaline catalyst into the three-necked flask at a speed of 200 rpm, adjusting the pH value to 7.5-8.0, adding polyvinyl alcohol and urea into the three-necked flask, raising the temperature to 90-95° C., reacting for 20-60 minutes, adding phytic acid solution into the three-necked flask to adjust the pH to 3.8-4.6, reacting for 20-40 minutes, adjusting the pH to 7.0-7.5 with a sodium hydroxide solution, and then adding urea, melamine and glycerol ether, maintaining the temperature at 88-93° C., adjusting the pH to 10-11.5 with a sodium hydroxide solution, reacting for 10-25 minutes, adding urea to react for 5-15 minutes, adjusting the pH to 7.5-8.5, cooling to 25-35° C., and adjusting the viscosity to 100-400 mPa·s to obtain a modified urea-formaldehyde resin adhesive;
[0017] Step 2, preparation of adhesive: grinding and sieving the layered silicate mineral dispersion, then stirring and heating with sodium hydroxide solution to obtain a modified layered silicate mineral dispersion suspension, repeatedly washing with deionized water to obtain a modified layered silicate mineral dispersion; weighing the modifier and the modified layered silicate mineral dispersion into a three-necked flask, stirring and drying, weighing the modified urea-formaldehyde resin adhesive, the dried modified layered silicate mineral and hydroxyethyl starch, mechanically stirring evenly, stirring at 300 rpm for 10 minutes in a constant temperature water bath at 25°C to obtain an adhesive. The mass ratio of the layered silicate mineral to the sodium hydroxide solution is (2-15):100, and the mass fraction of the sodium hydroxide solution is 10wt%.
[0018] In order to better realize the above technical scheme, in the second step of the preparation method of the smoke-suppressed and low-toxic adhesive for blockboard of the present invention, the heating mixing temperature is 40-90°C, the drying time is 30-180min, and the drying temperature is 40-90°C.
[0019] The third purpose of the present invention is to provide an application of an adhesive for smoke-suppressed and low-toxic blockboard, the technical point of which is that the eucalyptus board core is made of fast-growing eucalyptus core square strips of 9.5mm×17mm, the board core thickness is 9.5mm, the moisture content is 4-6%, and the eucalyptus veneer is fast-growing eucalyptus rotary cut veneer, the thickness is 3mm, and the moisture content is 7-8%.) The pressing process is used to press a three-layer blockboard with a width specification of 300mm×350mm and a thickness of 14mm (the upper and lower surface layers are both 3mm thick eucalyptus veneers, and the board core is eucalyptus core). The board core is double-sidedly coated with glue, and the glue coating amount is 180-250g / m 2 After gluing, open aging is carried out for 10-30 minutes, closed aging is carried out for 30-60 minutes, and then cold pressing is carried out (pre-pressing time is 30-150 minutes, unit pressure is 0.8MPa), and then hot pressing is carried out (hot pressing time is 10-15 minutes, unit pressure is 1.2MPa, temperature is 120-140℃).
[0020] Compared with the prior art, the smoke-suppressing and low-toxicity adhesive for blockboard, the preparation method and the application thereof of the present invention can achieve the following beneficial effects:
[0021] 1. Phytic acid is an environmentally friendly, non-toxic, cheap, easily available and bio-affinity organic phosphoric acid flame retardant, containing up to 28% of the total molecular weight of phosphorus atoms. During the combustion process, the phosphoric acid groups in phytic acid will decompose into phosphoric acid and metaphosphate and be released, and catalyze the wood to form a stable carbon layer. At the same time, it is compounded with silicate minerals with modified layered structures. The silicate minerals with modified layered structures begin to gradually decompose when the temperature exceeds 300°C, absorb environmental heat, and inhibit the thermal degradation reaction of artificial boards; the water released by decomposition can not only reduce the surface temperature of the material, but also dilute the combustion gas. The magnesium oxide generated by decomposition has a large surface area, can adsorb pyrolysis intermediates, and reduce the combustion intensity and smoke generation. Therefore, the smoke-suppressing and low-toxic adhesive for blockboards of the present invention has good flame retardant effect and smoke suppression effect, and the flame retardant performance reaches B1 level, the smoke release is low, and it can reach ZA2 level after the mouse poisoning test.
[0022] 2. The modified layered silicate minerals are modified by cationic surfactants, which reduces the agglomeration phenomenon and improves the dispersibility of the modified layered silicate minerals in the adhesive. Phytic acid is composed of 6 phosphate groups and 12 hydroxyl groups, and has a strong electronegativity. It can combine with metal ions and positively charged compounds to form a stable coordination network with the metal ions in the modified layered silicate minerals, thereby reducing the agglomeration phenomenon of the modified layered silicate minerals; making the flame retardant effect more uniform, reducing the amount of modified layered silicate minerals used, and ensuring the bonding strength of the artificial board. The prepared blockboard has the characteristics of high bonding strength.
[0023] 3. The adhesive is modified by using glycerol ether, and a structure containing an ether bond is introduced into the adhesive system. The epoxy groups at both ends of the structure can participate in the curing reaction of urea-formaldehyde resin and are closely connected with the resin matrix. The molecular structure contains flexible long fatty chains that can rotate freely and are elastic, which improves the toughness of the adhesive and reduces the brittleness of the adhesive caused by the addition of silicate minerals with modified layered structures. At the same time, the addition of epoxy groups improves the joint strength of the adhesive. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0025] Figure 1 It is the total heat release spectrum of Example 1, Example 4 and Comparative Example 1, Comparative Example 2, Comparative Example 4;
[0026] Figure 2 It is the total smoke release spectrum of Example 1, Example 4 and Comparative Example 1, Comparative Example 2, and Comparative Example 4. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the specific embodiments of the present invention and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0028] Unless otherwise specified, the materials, equipment, instruments, etc. used in the following examples can be obtained from commercial sources.
[0029] Example 1
[0030] 300 g of 37% formaldehyde solution was weighed and poured into a three-necked flask, the stirrer was turned on at a speed of 200 rpm, the pH value of the formaldehyde solution was adjusted to 7.5-8.0 using a sodium hydroxide solution (30 wt%), 5 g of polyvinyl alcohol and 140 g of urea were added, the temperature of the three-necked flask was raised to 95° C., after reacting for 30 min, phytic acid solution (50 wt%) was added to the three-necked flask to adjust the pH to 3.4-4.6, after reacting for 20 min, the pH was adjusted to 7.0-7.5 using a sodium hydroxide solution (30 wt%), 60 g of urea, 30 g of melamine, and 20 parts of 1,4-butanediol glycidyl ether were added, the temperature was maintained at 88-93° C., the pH was adjusted to 8-8.5 using a sodium hydroxide solution (30 wt%), and the reaction was continued for 25 min. After adding 20g of urea and reacting for 10 minutes, the pH is adjusted to 7.5-8.5, the reactant is cooled to 25-35°C, and the viscosity is 100-400mPa·s to obtain a modified urea-formaldehyde resin adhesive.
[0031] Weigh 100g of modified urea-formaldehyde resin adhesive, 30g of modified brucite, and 3g of hydroxyethyl starch, stir them evenly mechanically, and stir them at 300rmp for 10min in a constant temperature water bath at 25°C to obtain an adhesive for blockboard with smoke suppression and low toxicity.
[0032] The eucalyptus board core is made of fast-growing eucalyptus core square strips 9.5mm×17mm, the board core thickness is 9.5mm, the moisture content is 5%, and the eucalyptus veneer is fast-growing eucalyptus peeled veneer, the thickness is 3mm, and the moisture content is 8%.) The pressing process is used to press the three-layer blockboard with a width specification of 300mm×350mm and a thickness of 14mm (the upper and lower surfaces are both 3mm thick eucalyptus veneers, and the board core is eucalyptus core). The board core is double-sided coated with smoke-suppressing and low-toxic blockboard adhesive, and the glue coating amount is 220g / m 2 After gluing, the open-mouth aging is carried out for 10 minutes, the closed-mouth aging is carried out for 30 minutes, and then cold pressing is carried out (pre-pressing time is 60 minutes, unit pressure is 0.8MPa), and then hot pressing is carried out (hot pressing time is 15 minutes, unit pressure is 1.2MPa, temperature is 120℃).
[0033] Example 2: Compared with Example 1, the alkaline catalyst sodium hydroxide is changed to potassium hydroxide.
[0034] Weigh 300g of 37% formaldehyde solution and pour it into a three-necked flask, turn on the stirrer at a speed of 200 rpm, use potassium hydroxide solution (30wt%) to adjust the pH value of the formaldehyde solution to 7.5-8.0, add 5g of polyvinyl alcohol and 140g of urea, and then raise the temperature of the three-necked flask to 95°C. After reacting for 30 minutes, add phytic acid solution (50wt%) into the three-necked flask to adjust the pH to 3.4-4.6, react for 20 minutes, and then use sodium hydroxide solution (30wt%) to adjust the pH to 7.0-7.5, add 60g of urea, 30g of melamine, and 20 parts of 1,4-butanediol glycidyl ether, keep the temperature at 88-93°C, use sodium hydroxide solution (30wt%) to adjust the pH to 8-8.5, and react for 25 minutes. After adding 20g of urea and reacting for 10 minutes, the pH is adjusted to 7.5-8.5, the reactant is cooled to 25-35°C, and the viscosity is 100-400mPa·s to obtain a modified urea-formaldehyde resin adhesive.
[0035] Weigh 100g of modified urea-formaldehyde resin adhesive, 30g of modified brucite, and 3g of hydroxyethyl starch, stir them evenly mechanically, and stir them at 300rmp for 10min in a constant temperature water bath at 25°C to obtain an adhesive for blockboard with smoke suppression and low toxicity.
[0036] The eucalyptus board core is made of fast-growing eucalyptus core square strips 9.5mm×17mm, the board core thickness is 9.5mm, the moisture content is 5%, and the eucalyptus veneer is fast-growing eucalyptus peeled veneer, the thickness is 3mm, and the moisture content is 8%.) The pressing process is used to press the three-layer blockboard with a width specification of 300mm×350mm and a thickness of 14mm (the upper and lower surfaces are both 3mm thick eucalyptus veneers, and the board core is eucalyptus core). The board core is double-sided coated with smoke-suppressing and low-toxic blockboard adhesive, and the glue coating amount is 220g / m 2 After gluing, the open-mouth aging is carried out for 10 minutes, the closed-mouth aging is carried out for 30 minutes, and then cold pressing is carried out (pre-pressing time is 60 minutes, unit pressure is 0.8MPa), and then hot pressing is carried out (hot pressing time is 15 minutes, unit pressure is 1.2MPa, temperature is 120℃).
[0037] Example 3: Compared with Example 1, 1,4-butanediol glycidyl ether is replaced by propylene glycol triglycidyl ether
[0038] Weigh 300g of 37% formaldehyde solution and pour it into a three-necked flask, turn on the stirrer at a speed of 200 rpm, use sodium hydroxide solution (30wt%) to adjust the pH value of the formaldehyde solution to 7.5-8.0, add 5g of polyvinyl alcohol and 140g of urea, and then raise the temperature of the three-necked flask to 95°C. After reacting for 30min, add phytic acid solution (50wt%) into the three-necked flask to adjust the pH to 3.4-4.6, react for 20min, and then use sodium hydroxide solution (30wt%) to adjust the pH to 7.0-7.5, add 60g of urea, 30g of melamine, and 20 parts of propylene glycol triglycidyl ether, keep the temperature at 88-93°C, use sodium hydroxide solution (30wt%) to adjust the pH to 8-8.5, and react for 25min. After adding 20g of urea and reacting for 10 minutes, the pH is adjusted to 7.5-8.5, the reactant is cooled to 25-35°C, and the viscosity is 100-400mPa·s to obtain a modified urea-formaldehyde resin adhesive.
[0039] Weigh 100g of modified urea-formaldehyde resin adhesive, 30g of modified brucite, and 3g of hydroxyethyl starch, stir them evenly mechanically, and stir them at 300rmp for 10min in a constant temperature water bath at 25°C to obtain an adhesive for blockboard with smoke suppression and low toxicity.
[0040] The eucalyptus board core is made of fast-growing eucalyptus core square strips 9.5mm×17mm, the board core thickness is 9.5mm, the moisture content is 5%, and the eucalyptus veneer is fast-growing eucalyptus peeled veneer, the thickness is 3mm, and the moisture content is 8%.) The pressing process is used to press the three-layer blockboard with a width specification of 300mm×350mm and a thickness of 14mm (the upper and lower surfaces are both 3mm thick eucalyptus veneers, and the board core is eucalyptus core). The board core is double-sided coated with smoke-suppressing and low-toxic blockboard adhesive, and the glue coating amount is 220g / m 2 After gluing, the open-mouth aging is carried out for 10 minutes, the closed-mouth aging is carried out for 30 minutes, and then cold pressing is carried out (pre-pressing time is 60 minutes, unit pressure is 0.8MPa), and then hot pressing is carried out (hot pressing time is 15 minutes, unit pressure is 1.2MPa, temperature is 120℃).
[0041] Example 4: Compared with Example 1, brucite is replaced by sepiolite
[0042] 300 g of 37% formaldehyde solution was weighed and poured into a three-necked flask, the stirrer was turned on at a speed of 200 rpm, the pH value of the formaldehyde solution was adjusted to 7.5-8.0 using a sodium hydroxide solution (30 wt%), 5 g of polyvinyl alcohol and 140 g of urea were added, the temperature of the three-necked flask was raised to 95° C., after reacting for 30 min, phytic acid solution (50 wt%) was added to the three-necked flask to adjust the pH to 3.4-4.6, after reacting for 20 min, the pH was adjusted to 7.0-7.5 using a sodium hydroxide solution (30 wt%), 60 g of urea, 30 g of melamine, and 20 parts of 1,4-butanediol glycidyl ether were added, the temperature was maintained at 88-93° C., the pH was adjusted to 8-8.5 using a sodium hydroxide solution (30 wt%), and the reaction was continued for 25 min. After adding 20g of urea and reacting for 10 minutes, the pH is adjusted to 7.5-8.5, the reactant is cooled to 25-35°C, and the viscosity is 100-400mPa·s to obtain a modified urea-formaldehyde resin adhesive.
[0043] Weigh 100g of modified urea-formaldehyde resin adhesive, 30g of modified sepiolite, and 3g of hydroxyethyl starch, stir them evenly mechanically, and stir them at 300rmp for 10min in a constant temperature water bath at 25°C to obtain an adhesive for blockboard with smoke suppression and low toxicity.
[0044] The eucalyptus board core is made of fast-growing eucalyptus core square strips 9.5mm×17mm, the board core thickness is 9.5mm, the moisture content is 5%, and the eucalyptus veneer is fast-growing eucalyptus peeled veneer, the thickness is 3mm, and the moisture content is 8%.) The pressing process is used to press the three-layer blockboard with a width specification of 300mm×350mm and a thickness of 14mm (the upper and lower surfaces are both 3mm thick eucalyptus veneers, and the board core is eucalyptus core). The board core is double-sided coated with smoke-suppressing and low-toxic blockboard adhesive, and the glue coating amount is 220g / m 2 After gluing, the open-mouth aging is carried out for 10 minutes, the closed-mouth aging is carried out for 30 minutes, and then cold pressing is carried out (pre-pressing time is 60 minutes, unit pressure is 0.8MPa), and then hot pressing is carried out (hot pressing time is 15 minutes, unit pressure is 1.2MPa, temperature is 120℃).
[0045] Comparative Example 1: replacing phytic acid with ammonium chloride;
[0046] Weigh 300g of 37% formaldehyde solution and pour it into a three-necked flask, turn on the stirrer at a speed of 200 rpm, use sodium hydroxide solution (30wt%) to adjust the pH value of the formaldehyde solution to 7.5-8.0, add 5g of polyvinyl ammonium chloride solution (30wt%) to adjust the pH to 3.4-4.6, react for 20 minutes, use sodium hydroxide solution (30wt%) to adjust the pH to 7.0-7.5, add 60g of urea, 30g of melamine, and 20 parts of 1,4-butanediol glycidyl ether, keep the temperature at 88-93°C, use sodium hydroxide solution (30wt%) to adjust the pH to 8-8.5, react for 25 minutes. Add 20g of urea and react for 10 minutes, then adjust the pH to 7.5-8.5, cool the reactant to 25-35°C, and the viscosity is 100-400mPa·s to obtain a modified urea-formaldehyde resin adhesive.
[0047] Weigh 100g of modified urea-formaldehyde resin adhesive, 30g of modified brucite, and 3g of hydroxyethyl starch, stir them evenly mechanically, and stir them at 300rmp for 10min in a constant temperature water bath at 25°C to obtain an adhesive for blockboard with smoke suppression and low toxicity.
[0048] The eucalyptus board core is made of fast-growing eucalyptus core square strips 9.5mm×17mm, the board core thickness is 9.5mm, the moisture content is 5%, and the eucalyptus veneer is fast-growing eucalyptus peeled veneer, the thickness is 3mm, and the moisture content is 8%.) The pressing process is used to press the three-layer blockboard with a width specification of 300mm×350mm and a thickness of 14mm (the upper and lower surfaces are both 3mm thick eucalyptus veneers, and the board core is eucalyptus core). The board core is double-sided coated with smoke-suppressing and low-toxic blockboard adhesive, and the glue coating amount is 220g / m 2 After gluing, the open-mouth aging is carried out for 10 minutes, the closed-mouth aging is carried out for 30 minutes, and then cold pressing is carried out (pre-pressing time is 60 minutes, unit pressure is 0.8MPa), and then hot pressing is carried out (hot pressing time is 15 minutes, unit pressure is 1.2MPa, temperature is 120℃).
[0049] Comparative Example 2: No Melamine
[0050] Weigh 300g of 37% formaldehyde solution and pour it into a three-necked flask, turn on the stirrer at a speed of 200 rpm, use sodium hydroxide solution (30wt%) to adjust the pH value of the formaldehyde solution to 7.5-8.0, add 5g of polyvinyl alcohol and 140g of urea, and then raise the temperature of the three-necked flask to 95°C. After reacting for 30 minutes, add phytic acid solution (50wt%) into the three-necked flask to adjust the pH to 3.4-4.6, react for 20 minutes, and then use sodium hydroxide solution (30wt%) to adjust the pH to 7.0-7.5, add 60g of urea and 20 parts of 1,4-butanediol glycidyl ether, keep the temperature at 88-93°C, use sodium hydroxide solution (30wt%) to adjust the pH to 8-8.5, and react for 25 minutes. After adding 20g of urea and reacting for 10 minutes, the pH is adjusted to 7.5-8.5, the reactant is cooled to 25-35°C, and the viscosity is 100-400mPa·s to obtain a modified urea-formaldehyde resin adhesive.
[0051] Weigh 100g of modified urea-formaldehyde resin adhesive, 30g of modified brucite, and 3g of hydroxyethyl starch, stir them evenly mechanically, and stir them at 300rmp for 10min in a constant temperature water bath at 25°C to obtain an adhesive for blockboard with smoke suppression and low toxicity.
[0052] The eucalyptus board core is made of fast-growing eucalyptus core square strips 9.5mm×17mm, the board core thickness is 9.5mm, the moisture content is 5%, and the eucalyptus veneer is fast-growing eucalyptus peeled veneer, the thickness is 3mm, and the moisture content is 8%.) The pressing process is used to press the three-layer blockboard with a width specification of 300mm×350mm and a thickness of 14mm (the upper and lower surfaces are both 3mm thick eucalyptus veneers, and the board core is eucalyptus core). The board core is double-sided coated with smoke-suppressing and low-toxic blockboard adhesive, and the glue coating amount is 220g / m 2 After gluing, the open-mouth aging is carried out for 10 minutes, the closed-mouth aging is carried out for 30 minutes, and then cold pressing is carried out (pre-pressing time is 60 minutes, unit pressure is 0.8MPa), and then hot pressing is carried out (hot pressing time is 15 minutes, unit pressure is 1.2MPa, temperature is 120℃).
[0053] Comparative Example 3: No Glyceryl Ether
[0054] Weigh 300g of 37% formaldehyde solution and pour it into a three-necked flask, turn on the stirrer at a speed of 200 rpm, use sodium hydroxide solution (30wt%) to adjust the pH value of the formaldehyde solution to 7.5-8.0, add 5g of polyvinyl alcohol and 140g of urea, and then raise the temperature of the three-necked flask to 95°C. After reacting for 30min, add phytic acid solution (50wt%) into the three-necked flask to adjust the pH to 3.4-4.6, react for 20min, and then use sodium hydroxide solution (30wt%) to adjust the pH to 7.0-7.5, add 60g of urea and 30g of melamine, keep the temperature at 88-93°C, use sodium hydroxide solution (30wt%) to adjust the pH to 8-8.5, and react for 25min. After adding 20g of urea and reacting for 10 minutes, the pH is adjusted to 7.5-8.5, the reactant is cooled to 25-35°C, and the viscosity is 100-400mPa·s to obtain a modified urea-formaldehyde resin adhesive.
[0055] Weigh 100g of modified urea-formaldehyde resin adhesive, 30g of modified brucite, and 3g of hydroxyethyl starch, stir them evenly mechanically, and stir them at 300rmp for 10min in a constant temperature water bath at 25°C to obtain an adhesive for blockboard with smoke suppression and low toxicity.
[0056] The eucalyptus board core is made of fast-growing eucalyptus core square strips 9.5mm×17mm, the board core thickness is 9.5mm, the moisture content is 5%, and the eucalyptus veneer is fast-growing eucalyptus peeled veneer, the thickness is 3mm, and the moisture content is 8%.) The pressing process is used to press the three-layer blockboard with a width specification of 300mm×350mm and a thickness of 14mm (the upper and lower surfaces are both 3mm thick eucalyptus veneers, and the board core is eucalyptus core). The board core is double-sided coated with smoke-suppressing and low-toxic blockboard adhesive, and the glue coating amount is 220g / m 2 After gluing, the open-mouth aging is carried out for 10 minutes, the closed-mouth aging is carried out for 30 minutes, and then cold pressing is carried out (pre-pressing time is 60 minutes, unit pressure is 0.8MPa), and then hot pressing is carried out (hot pressing time is 15 minutes, unit pressure is 1.2MPa, temperature is 120℃).
[0057] Comparative Example 4: Silicate minerals with unmodified layered structures
[0058] 300 g of 37% formaldehyde solution was weighed and poured into a three-necked flask, the stirrer was turned on at a speed of 200 rpm, the pH value of the formaldehyde solution was adjusted to 7.5-8.0 using a sodium hydroxide solution (30 wt%), 5 g of polyvinyl alcohol and 140 g of urea were added, the temperature of the three-necked flask was raised to 95° C., after reacting for 30 min, phytic acid solution (50 wt%) was added to the three-necked flask to adjust the pH to 3.4-4.6, after reacting for 20 min, the pH was adjusted to 7.0-7.5 using a sodium hydroxide solution (30 wt%), 60 g of urea, 30 g of melamine, and 20 parts of 1,4-butanediol glycidyl ether were added, the temperature was maintained at 88-93° C., the pH was adjusted to 8-8.5 using a sodium hydroxide solution (30 wt%), and the reaction was continued for 25 min. After adding 20g of urea and reacting for 10 minutes, the pH is adjusted to 7.5-8.5, the reactant is cooled to 25-35°C, and the viscosity is 100-400mPa·s to obtain a modified urea-formaldehyde resin adhesive.
[0059] Weigh 100g of modified urea-formaldehyde resin adhesive, 30g of flour, and 3g of hydroxyethyl starch, stir them evenly mechanically, and stir them at 300rmp for 10min in a constant temperature water bath at 25°C to obtain an adhesive for blockboard with smoke suppression and low toxicity.
[0060] The eucalyptus board core is made of fast-growing eucalyptus core square strips 9.5mm×17mm, the board core thickness is 9.5mm, the moisture content is 5%, and the eucalyptus veneer is fast-growing eucalyptus peeled veneer, the thickness is 3mm, and the moisture content is 8%.) The pressing process is used to press the three-layer blockboard with a width specification of 300mm×350mm and a thickness of 14mm (the upper and lower surfaces are both 3mm thick eucalyptus veneers, and the board core is eucalyptus core). The board core is double-sided coated with smoke-suppressing and low-toxic blockboard adhesive, and the glue coating amount is 220g / m 2 After gluing, the open-mouth aging is carried out for 10 minutes, the closed-mouth aging is carried out for 30 minutes, and then cold pressing is carried out (pre-pressing time is 60 minutes, unit pressure is 0.8MPa), and then hot pressing is carried out (hot pressing time is 15 minutes, unit pressure is 1.2MPa, temperature is 120℃).
[0061] Test example
[0062] The results of the glue storage period (GB / T14074-2017), board formaldehyde emission, bonding strength test (GB / T17657-2022), cone calorimeter flame retardancy test, and smoke toxicity evaluation (GB / T 20285-2006) obtained in Examples 1-4 and Comparative Examples 1-4 are shown in Table 1:
[0063] Table 1 Test results
[0064]
[0065]
[0066] It can be concluded from the test results in Table 1 that the flame retardant properties of the embodiment are significantly improved compared with the comparative example. By comparing the combustion performance test results of the embodiment with that of comparative example 4, it can be concluded that the addition of silicate minerals with modified layered structures and phytic acid can effectively improve the overall flame retardant properties of the flame retardant rubber.
[0067] Phytic acid is composed of 6 phosphate groups and 12 hydroxyl groups, and has strong electronegativity. It can combine with metal ions and positively charged compounds, and form a stable coordination network with metal ions in brucite, reducing the agglomeration of brucite. At high temperatures, the phosphate groups in phytic acid will decompose into phosphoric acid and metaphosphate, which will be released and catalyze the wood material to form a stable carbon layer, protecting the lower layer from burning, thereby improving the flame retardant properties of the material. At the same time, the hydrate of the modified layered silicate mineral decomposes under high temperature conditions to produce a large amount of water vapor, which reduces the surface temperature, dilutes oxygen, slows down the combustion reaction rate, and has an effective smoke suppression effect.
[0068] The results of Example 3 and Comparative Example 3 show that the addition of 1,4-butanediol glycidyl ether or propylene glycol triglycidyl ether can effectively improve the bonding strength of the adhesive, and the water resistance is also greatly improved. The ether bond in 1,4-butanediol glycidyl ether is a flexible segment. After adding the flexible segment, a larger free space is generated, which softens the cross-linked segment, absorbs energy while being subjected to tensile stress, and has a toughening effect. The epoxy groups carried thereby improve the bonding strength. Glycidyl ether can reduce more hydrophilic groups, and more cross-linked structures are generated in the resin, and the water resistance of urea-formaldehyde resin is enhanced, so the bonding strength is improved.
[0069] The formaldehyde emission of Comparative Example 2 is significantly higher than that of Example 1, because the aldehyde-preventing agent reduces the further release of free formaldehyde by the aldehyde-preventing agent, resulting in a high free formaldehyde content. The formaldehyde emission of Comparative Example 3 is significantly lower than that of Example 1, because the ether alkali content in the added toughening modifier is relatively high, which increases the ether bonds in the urea-formaldehyde resin and makes the ether bonds unstable. The ether bond breakage during the hot pressing process will be accompanied by the release of formaldehyde. Comparative Example 3 does not add toughening agent modification, and the formaldehyde content is relatively low.
[0070] Figure 1The total heat release spectrum of Example 1, Example 4 and Comparative Example 1, Comparative Example 2, Comparative Example 4. The total heat release of Example 1 and Example 4 is significantly reduced compared with Comparative Example 4. The layered silicate alleviates the diffusion of external oxygen into the material, reduces the further combustion, and reduces the total heat release rate. The total heat release of Example 1 and Example 4 is also significantly reduced compared with Comparative Example 1. Phytic acid contains two reactive hydroxyl groups, which can interact with metal ions to form phytate. Phytic acid with negatively charged phosphate groups can combine with metal ions and other positively charged flame retardants, and is compounded with layered silicate to achieve synergistic flame retardancy, thereby reducing the total heat release rate.
[0071] Figure 2 The total smoke release spectra of Example 1, Example 4 and Comparative Example 1, Comparative Example 2, and Comparative Example 4. The total smoke release of Example 1 and Example 4 is significantly reduced compared to Comparative Example 4. The layered silicate sheet has a good gas-liquid barrier function. During the combustion of the material, the layered silicate sheet located on the combustion surface will block the migration of combustible small molecules to the combustion interface, alleviating the diffusion of external oxygen into the material. The total smoke release of Example 1 and Example 4 is also significantly reduced compared to Comparative Example 1. Phytic acid can decompose small molecular phosphoric acid substances at about 200°C, promote the dehydration and carbonization of the polymer, and obtain a stable protective layer. At the same time, the PO· and HPO· free radicals generated during the decomposition of phytic acid can capture H· and OH·, thereby effectively terminating the combustion chain reaction and reducing the total amount of smoke generated.
[0072] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A smoke-suppressing and low-toxicity adhesive for blockboard, characterized in that: The invention comprises 100 parts by weight of a modified urea-formaldehyde resin adhesive and 30-50 parts by weight of a mixed filler; the modified urea-formaldehyde resin adhesive comprises 300 parts by weight of a formaldehyde aqueous solution with a mass fraction of 25-50wt%, 10-30 parts by weight of an alkaline catalyst, 1-5 parts by weight of polyvinyl alcohol, 160-250 parts by weight of urea, 10-20 parts by weight of a phytic acid solution with a mass fraction of 50wt%, 10-30 parts by weight of sodium hydroxide with a mass fraction of 30-50wt%, 20-50 parts by weight of melamine and 10-30 parts by weight of glycerol ether.
2. The smoke-suppressing and low-toxicity adhesive for blockboard according to claim 1, characterized in that: The glycerol ether is 1,4-butanediol glycidyl ether and at least one of glycerol triglycidyl ether.
3. The smoke-suppressing and low-toxicity adhesive for blockboard according to claim 1, characterized in that: The alkaline catalyst is at least one of sodium hydroxide and potassium hydroxide.
4. The smoke-suppressed and low-toxicity adhesive for blockboard according to claim 1, characterized in that: The mixed filler is a mixture of a silicate mineral with a modified layered structure and hydroxyethyl starch, and the mass ratio of the silicate mineral with a modified layered structure to the hydroxyethyl starch is 10:
1.
5. The smoke-suppressed and low-toxicity adhesive for blockboard according to claim 4, characterized in that: The modified layered silicate mineral comprises a mixture of the layered silicate mineral and a modifier, and the added amount of the modifier is 0.5-5wt% of the layered silicate mineral.
6. The smoke-suppressing and low-toxicity adhesive for blockboard according to claim 5, characterized in that: The layered silicate mineral is at least one of brucite and sepiolite.
7. The smoke-suppressing and low-toxicity adhesive for blockboard according to claim 5, characterized in that: The modifier is a cationic surfactant such as dodecyl dimethyl benzyl ammonium chloride.
8. A method for preparing a smoke-suppressed and low-toxicity blockboard adhesive according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1, pouring the formaldehyde solution into a three-necked flask, adding an alkaline catalyst into the three-necked flask at a speed of 200 rpm, adjusting the pH value to 7.5-8.0, adding polyvinyl alcohol and urea into the three-necked flask, raising the temperature to 90-95° C., reacting for 20-60 minutes, adding phytic acid solution into the three-necked flask to adjust the pH to 3.8-4.6, reacting for 20-40 minutes, adjusting the pH to 7.0-7.5 with a sodium hydroxide solution, and then adding urea, melamine and glycerol ether, maintaining the temperature at 88-93° C., adjusting the pH to 10-11.5 with a sodium hydroxide solution, reacting for 10-25 minutes, adding urea to react for 5-15 minutes, adjusting the pH to 7.5-8.5, cooling to 25-35° C., and adjusting the viscosity to 100-400 mPa·s to obtain a modified urea-formaldehyde resin adhesive; Step 2, preparation of adhesive: grinding and sieving the layered silicate mineral dispersion, then stirring and heating with sodium hydroxide solution to obtain a modified layered silicate mineral dispersion suspension, repeatedly washing with deionized water to obtain a modified layered silicate mineral dispersion; weighing the modifier and the modified layered silicate mineral dispersion into a three-necked flask, stirring and drying, weighing the modified urea-formaldehyde resin adhesive, the dried modified layered silicate mineral and hydroxyethyl starch, mechanically stirring evenly, stirring at 300 rpm for 10 minutes in a constant temperature water bath at 25°C to obtain an adhesive.
9. The method for preparing a smoke-suppressed and low-toxicity adhesive for blockboard according to claim 5, characterized in that: In the step 2, the heating and mixing temperature is 40-90°C, the drying time is 30-180min, and the drying temperature is 40-90°C.
10. An application of an adhesive for smoke-suppressed and low-toxic blockboard, characterized in that: The amount of the smoke-suppressing and low-toxic blockboard adhesive in the blockboard is 180-250 g / m 2 .
Citation Information
Patent Citations
A flame retardant impregnation treatment process for refractory pine wood
CN103481343B
A method for preparing flame-retardant wood with in-situ polymerized aniline
CN114102776B
A method for preparing flame-retardant plywood
CN114350293B